Seeking crops with balanced parts for the ideal whole - Abbai, Ragavendran; Singh, Vikas K.; Snowdon, Rod J.; Kumar, Arvind; Schnurbusch, Thorsten (Elsevier, 2020)
Crop domestication and breeding considerably increased productivity over centuries but unconsciously lowered ‘selfish plant behavior’ or individual plant fitness. Paradoxically, enhancing individual plant fitness is mistakenly equated with crop improvement. Because agriculture relies on community performance, embracing an agroecological genetics and genomics viewpoint might maximize communal yield by matching crop genotypes to target environments.